2021
DOI: 10.3224/zehf.v4i1.06
|View full text |Cite
|
Sign up to set email alerts
|

Unterschiedlich motiviert für das Studium: Motivationale Profile von Studierenden und ihre Zusammenhänge mit demografischen Merkmalen, Lernverhalten und Befinden

Abstract: Auf der Basis eines multidimensionalen Verständnisses von Studienmotivation wird ein Zusammenspiel motivationaler Variablen verschiedener Phasen des Studiums im Hinblick auf akademische Erfolgskriterien angenommen. Jedoch gibt es hierzu bislang keine empirische Evidenz. In der vorliegenden Studie wurde das Ziel verfolgt, das intraindividuelle Zusammenspiel intrinsischer und extrinsischer Studienwahlmotivation als Variablen der Studienvorphase sowie des akademischen Selbstkonzepts und der akademischen Selbstwir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 47 publications
1
5
0
1
Order By: Relevance
“…Our results showed a significant decrease for all three subdimensions of study satisfaction over the course of both the summer semester 2020 and fall semester 2020/2021. The decreasing trend found in our study is comparable to Scheunemann et al (2021) although the drop in the means of the subdimensions over time were generally more during the pandemic. Our finding supports the understanding that study satisfaction is a subjectively assessed experience which could be dependent on and shaped by situations like the COVID-19 pandemic.…”
Section: Changes In the Dimensions Of Study Satisfactionsupporting
confidence: 80%
See 4 more Smart Citations
“…Our results showed a significant decrease for all three subdimensions of study satisfaction over the course of both the summer semester 2020 and fall semester 2020/2021. The decreasing trend found in our study is comparable to Scheunemann et al (2021) although the drop in the means of the subdimensions over time were generally more during the pandemic. Our finding supports the understanding that study satisfaction is a subjectively assessed experience which could be dependent on and shaped by situations like the COVID-19 pandemic.…”
Section: Changes In the Dimensions Of Study Satisfactionsupporting
confidence: 80%
“…On a descriptive level, a few findings indicated a slight linear increase in overall study satisfaction over a period of 4 months (Ng and Ye, 2016) and 6 months (Allan et al, 2020) without considering the subdimensions. Contrary, Scheunemann et al (2021) found a decrease in overall study satisfaction over one semester. Currently, during the COVID-19 pandemic, decreases in study satisfaction are conceivable as students are exposed to several pandemic-related challenges (Sahu, 2020).…”
Section: Study Satisfactionmentioning
confidence: 57%
See 3 more Smart Citations